Effect of Red Bean Extract (Phaseolus vulgaris, L) on the Development of Female Mice Eggs (Mus musculus) Balb/C strains - Miftahul Hasanah; Syamsul Bahri; I Wayan Merta (Jurnal Penelitian Pendidikan IPA, 2020)
Research was conducted to study the effect of red bean extract (Phaseolus vulgaris, L) on the development of mouse egg follicles (Mus musculus) This study used a completely randomized design consisting of 4 treatment groups. Each treatment group used 5 female mice aged 2 months weighing 18-22 grams. The research parameters were the number of egg follicles at various stages of development which were observed from the histological incision of the ovarium. The data obtained were analyzed by Two Way Variance Analysis and DMRT Test. The results showed that the treatment of red bean extract had a significant effect on the development of egg follicles in mice with balb/c strains